2007
DOI: 10.1111/j.1464-5491.2007.02250.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the special needs of children with Type 1 diabetes in the school setting. An overview of parents’ perceptions

Abstract: Training sessions on Type 1 diabetes, an increase in the number of nurses, better availability of resources from diabetic associations to schools and improved communication between school personnel and parents were identified as key factors that may improve the full integration of the diabetic child in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
1
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(118 citation statements)
references
References 27 publications
7
102
1
8
Order By: Relevance
“…It suggests that Taiwan adolescents with T1DM do not perceive high levels of school support. Adolescents with T1DM often feel they are discriminated against by school personnel (Amillategui, Calle, Alvarez, Cardiel, & Barrio, 2007). School rules also disrupt glycemic control schedule of adolescents with T1DM (Hayes-Bohn, Neumark-Sztainer, Mellin, & Patterson, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…It suggests that Taiwan adolescents with T1DM do not perceive high levels of school support. Adolescents with T1DM often feel they are discriminated against by school personnel (Amillategui, Calle, Alvarez, Cardiel, & Barrio, 2007). School rules also disrupt glycemic control schedule of adolescents with T1DM (Hayes-Bohn, Neumark-Sztainer, Mellin, & Patterson, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Gjennom forsknings-og erfaringsbasert kunnskap om hva familier med kronisk syke har behov for ser vi verdien av å øke helsesøstres kunnskap. Slik kan de videreformidle kunnskap til ansatte i skole og barnehage (6,10).…”
Section: Litteratursøkunclassified
“…Besides peers' support, teachers' support is also important. A study found that 9 % of parents had to change glucose monitoring and 16% changed treatment administration because of lack of support from teachers (Amillategui et al, 2007). In fact, teachers in general need to be knowledgeable of hyperglycemia and hypoglycemia's episodes in order to assist the adolescent if needed.…”
Section: School Supportmentioning
confidence: 99%